A child's Christmas at St. Nicholas Circle - McKelvey, Douglas Kaine (Tommy Nelson, 1999)
When her brother mistakes a lost child for the special visitor for whom the town is waiting one Christmas Eve, Katie and her family experience the meaning of the holiday is a special way.